Economic Impacts of El Ni\~no Southern Oscillation: Evidence from the Colombian Coffee Market - Andrea Bastianin; Alessandro Lanza; Matteo Manera (Fondazione Eni Enrico Mattei (FEEM), 2016)
We develop a structural econometric model to study the impacts of El Ni\~no Southern Oscillation (ENSO) on Colombian coffee production, exports and price. Our empirical specification is consistent with an economic model of the coffee market that, in the short-run, is characterized by a downward-sloping demand curve and by a vertical supply curve. This allows the study of the effects of unpredictable innovations to ENSO on the Colombian coffee price, while controlling for shocks arising from both the supply and the demand-side of the market. We show that El Ni\~no events (i.e. positive shocks to ENSO) might be beneficial for production and exports and tend to decrease the price of coffee. On the contrary, La Ni\~na conditions (i.e. negative shocks to ENSO) depress coffee production and exports and increase price. However, the overall impact of ENSO shocks is small. In the short-run, ENSO shocks explain 2% of the fluctuations of coffee production and 0.2% of the variability of the price of coffee. In the long-run, these percentages rise to 8% and 6%, respectively. Both in the short-run and in the long-run, demand-side shocks are more relevant than supply-side shocks in explaining the dynamics of the price of coffee.
Keywords: C32; O13; Q02; Q11; Q54; 330; Coffee; Colombia; El Ni\~no; ENSO; La Ni\~na; Structural VAR